Identificación de bacterias patógenas oportunistas en útero de alpaca pre y poscópula - Dellepiane G., Helen (2018)
The aim of the present study was to identify bacteria present in the uterine mucosa of alpaca before and after the copula. Samples of uterine mucosa were taken (177 before and 60 after copulation). For the collection of the sample, metallic speculum and protected swabs were used to avoid sample contamination. The samples were conserved and transported to the laboratory in tubes with Stuart transport medium at 4 °C. Samples were cultured on blood agar and MacConkey agar at 37 °C for 24 h and bacterial identification was performed through biochemical tests. A total of 165 bacterial isolates and 29 yeasts in the pre-copula group and 64 bacterial isolates and 6 yeasts in the post-copula group were found. The bacteria most frequently isolated were E. coli (24.9%), Providencia stuartii (16.5%), Shigella sp (16.5%), Hafnia alvei (5.9%), Serratia rubidae (5.9%) and yeasts (14.8%).